TEACHERS BEHALF ON LANGUAGE TEST CONSTRUCTION - Ismail, Nyak Mutia; Yoestara, Marisa (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
There are four steps necessarily to be conducted when designing multiple-choice test items, namely setting the objective, building both concise stems and options, determining one correct answer, employing item indices to accept or discarding items (Brown, 2004). As a matter of fact, most teachers in Aceh are not very well-informed about the fourth step and they accept all items as they are. This study focuses on high school teachers who undergo all of the steps offered in the framework when constructing multiple-choice items for English summative test(s). The qualitative method using framework analysis was used in obtaining the data. A questionnaire was distributed to 15 teachers. The analysis process was carried out through three-step analysis (Miles, Huberman, Saldana, 2013). The results depict that the teachers hardly conduct the index determining step or try-outs when constructing a test. This implies that there is no empirical warrant that all items are worth tested and can be the fundamentals for decision-making when assessing and evaluating students test results.